If x0 and ,x=sq. root of (4xy-4y^2) then, in terms of y, : PS Archive
Check GMAT Club Decision Tracker for the Latest School Decision Releases http://gmatclub.com/AppTrack

 It is currently 18 Jan 2017, 13:09

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Events & Promotions

Events & Promotions in June
Open Detailed Calendar

If x0 and ,x=sq. root of (4xy-4y^2) then, in terms of y,

Author Message
Manager
Joined: 05 Sep 2007
Posts: 144
Location: New York
Followers: 1

Kudos [?]: 36 [0], given: 0

If x0 and ,x=sq. root of (4xy-4y^2) then, in terms of y,  [#permalink]

Show Tags

11 Mar 2008, 17:54
00:00

Difficulty:

(N/A)

Question Stats:

100% (01:47) correct 0% (00:00) wrong based on 4 sessions

HideShow timer Statistics

This topic is locked. If you want to discuss this question please re-post it in the respective forum.

If x≠0 and ,x=sq. root of (4xy-4y^2) then, in terms of y, x=?
(A) 2y
(B) y
(C)
(D)
(E) –2y
Senior Manager
Joined: 15 Aug 2007
Posts: 252
Schools: Chicago Booth
Followers: 1

Kudos [?]: 69 [0], given: 0

Show Tags

11 Mar 2008, 18:56
A

Square on both sides and the equation becomes (x-2y)^2=0 => x=2y
Director
Joined: 14 Aug 2007
Posts: 733
Followers: 10

Kudos [?]: 180 [0], given: 0

Show Tags

11 Mar 2008, 19:23
el1981 wrote:
If x≠0 and ,x=sq. root of (4xy-4y^2) then, in terms of y, x=?
(A) 2y
(B) y
(C)
(D)
(E) –2y

A. results in x^2-4xy+4y^2=0 => (x-2y)^2 = 0 => x = 2y
CEO
Joined: 29 Mar 2007
Posts: 2583
Followers: 19

Kudos [?]: 421 [1] , given: 0

Show Tags

11 Mar 2008, 19:52
1
KUDOS
el1981 wrote:
If x≠0 and ,x=sq. root of (4xy-4y^2) then, in terms of y, x=?
(A) 2y
(B) y
(C)
(D)
(E) –2y

x=sqrt(4xy-4y^2) --> x^2=4xy-4y^2 --> x^2-4xy+4y^2=0 --> (x-2y)(x-2y)=0

x=2y

A
Re: PS: X,Y   [#permalink] 11 Mar 2008, 19:52
Display posts from previous: Sort by